DASTANS ARE THE MAIN GENRE OF KORAKALPOK FOLKLORE - Gulchira Khodjametova , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
All types of lyrical and epic works form the basis of Karakalpak folklore with its ancient and rich history. Lyrical genre works include folk, ceremonial songs (yor-yor, khaujar, joqlov, ramazan, gulapsan, badik, etc.), aytis (sayings, song-contests), proverbs and sayings, parables, quick sayings; works of epic genre include fairy tales, tales, folk tales, epics.